Penegakan Kode Etik Polisi Terhadap Pengaruh Citra Institusi Kepolisian - Andrea Nevada Daeng; Dyah Adriantini Sintha Dewi (Universitas Muhammadiyah Magelang, 2024)
The Code of Professional Ethics is one of the regulations made to protect the image of a profession. The Police Code of Ethics serves as a guide for police officers' behavior, but in practice, it is often ignored or not implemented properly, as stipulated in Law No. 2 of 2002 on the Indonesian National Police. The malfunction of the police code of ethics can have a negative impact on the image of the police institution in the eyes of the public. The purpose of this study is to evaluate the steps that have been taken and to identify the obstacles and difficulties faced by the Indonesian National Police (POLRI) in enforcing compliance with the code of ethics. This study uses a juridical-empirical method, conducting interviews and observations on several cases of police code of ethics malfunctions. The research results show that the malfunction of the police code of ethics has a significant impact on the decline of the police institution's image. Therefore, efforts are needed to increase awareness and compliance among police officers towards the police code of ethics, as well as to enhance supervision and sanctions for code of ethics violations.